2016
DOI: 10.1080/10428194.2016.1190970
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood chimerism and relapse after haplo-cord transplantation

Abstract: Haplo-cord stem cell transplantation combines the infusion of CD34 selected hematopoietic progenitors from a haplo-identical donor with an umbilical cord blood graft from an unrelated donor and allows faster count recovery, with low rates of disease recurrence and chronic GVHD. But the contribution of the umbilical cord blood graft to long-term transplant outcome remains unclear. We analyzed 39 recipients of haplo-cord transplants with AML and MDS, engrafted and in remission at 2 months. Median age was 66 (18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…5,6,16,18 Our own group has shown that persistence of the UCB graft (as contrasted with dominance of the haplo graft) is associated with improved outcomes. 7 Kwon et al, in their comparison of haplo vs haplo-cord, found that, despite higher DRI risk groups, haplo-cord did not have more relapse. 16 Wang et al, from China, also showed that the additional infusion of a CBU with a haplo-graft resulted in reduction of relapse rates and improved OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,16,18 Our own group has shown that persistence of the UCB graft (as contrasted with dominance of the haplo graft) is associated with improved outcomes. 7 Kwon et al, in their comparison of haplo vs haplo-cord, found that, despite higher DRI risk groups, haplo-cord did not have more relapse. 16 Wang et al, from China, also showed that the additional infusion of a CBU with a haplo-graft resulted in reduction of relapse rates and improved OS.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Many have observed decreases in relapse rates after UCB transplant that may be further enhanced by careful selection of the cord blood graft. [5][6][7] To hasten hematopoietic recovery after UCB transplant, double UCB grafts or in vitro expansion of UCB cells have been used, with varying success. 6,8 The delayed engraftment of cord blood cells can be readily avoided by third-party donor cells, usually derived from family members, but occasionally also from unrelated donors.…”
Section: Introductionmentioning
confidence: 99%
“…The patterns of chimerism by day 100, are similar to what has been previously described by our group and others. 15, 20, 39 The cumulative incidence of grade II/IV acute GVHD at day 100 was 9.3% and chronic GVHD at 2 years was only 8%. The incidence of both acute and chronic GVHD is lower than that of double cord blood transplant, as we have previously shown.…”
Section: Discussionmentioning
confidence: 98%
“…Our group also noted reduced rates of relapse associated with higher cord blood donor chimerism, similarly suggesting that cord engraftment mediates disease control. 11 Drawing from parallel multi-center Phase 2 trials, Brunstein et al 12 reported outcomes of double unit cord blood transplantation and unmanipulated haplo-marrow transplantation with reduce-intensity conditioning. The 1-year NRM and relapse rates were 24% and 31% in the double UCB transplantation trial, respectively, and 7 and 45%, respectively, in the haplo-marrow trial.…”
mentioning
confidence: 99%